Parental Perceptions of Islamic Religious Education in Boarding Schools and Children's Religious Character Development: A Case Study Approach - Dede Abdul Rohman; Hoerul Umam (Jurnal Iman dan Spiritualitas, 2026)
This study aims to analyze parents' perceptions of Islamic religious education in Islamic boarding schools in developing their children's religious character, using a case study of the Asy Syafi'iyah Islamic Boarding School in Garut. The research method used was a qualitative case study, with data collected through in-depth interviews, participatory observation, and documentation involving parents of students, the boarding school leadership, and teaching staff. The results indicate that the majority of parents have a very positive perception of the Islamic religious education system in Islamic boarding schools, particularly in terms of fostering worship, strengthening morals, and integrating religious and general education. Parents consider the religious, disciplined, and exemplary environment of Islamic boarding schools to be very effective in shaping their children's religious character. The findings also indicate that active parental involvement and intensive communication with the boarding school are important factors in maintaining the continuity of children's character development, both within the boarding school and within the family. However, maintaining the consistency of Islamic boarding school values when children return home poses challenges. This study concludes that positive parental perceptions and support for Islamic religious education in Islamic boarding schools significantly contribute to the successful formation of children's religious character. The results are expected to serve as a reference for developing synergy between Islamic boarding schools and families in children's character education.